2021
DOI: 10.18805/ajdfr.dr-187
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, Sensory and Microbiological Characteristics of Strawberry Flavored Milk under Refrigerated Storage

Abstract: Background: In this study, physico-chemical, sensory and microbial characteristics of three formulated strawberry flavored milk samples were investigated under 14 days of storage at refrigeration (4oC) temperature.Methods: pH, acidity, specific gravity, TSS, fat, protein, sensory attributes and microbial quality were investigated.Result: Physicochemical properties varied from pH (5.47 to 6.37), acidity (0.15 to 0.19%), TSS (15 to 16oBrix), specific gravity (1.05 to 1.063), fat (1.87 to 2.07%) and protein (3.33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Physicochemical, sensory, and microbial properties of new formulated strawberry‐flavored milks were evaluated during 14 days of storage at the refrigerator. Physicochemical properties and sensorial acceptance of strawberry‐flavored milk declined with the increase in time (Hossin et al., 2021). Jalilzadeh‐Afshari and Fadaei, (2021) reported that increasing the Gaz‐angubin content and bitter orange peel extract in flavored milk improved sensorial properties, viscosity, antioxidant activity, and total polyphenol content, while decreased total microbial count.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical, sensory, and microbial properties of new formulated strawberry‐flavored milks were evaluated during 14 days of storage at the refrigerator. Physicochemical properties and sensorial acceptance of strawberry‐flavored milk declined with the increase in time (Hossin et al., 2021). Jalilzadeh‐Afshari and Fadaei, (2021) reported that increasing the Gaz‐angubin content and bitter orange peel extract in flavored milk improved sensorial properties, viscosity, antioxidant activity, and total polyphenol content, while decreased total microbial count.…”
Section: Introductionmentioning
confidence: 99%
“…The protein content of the drinks sample was measured by using the micro Kjeldahl method reported with slight modification [10]. Twenty (20) ml of each sample was digested with 30ml of concentrated sulphuric acid using 2g of copper sulfate and 16.0g of sodium sulfate salt until a clear green solution was obtained.…”
Section: Determination Of Protein Contentmentioning
confidence: 99%